Women's words : the feminist practice of oral history - Gluck, Sherna Berger; Patai, Daphne (New York : Routledge, 1991)
Women's Words is the first collection of writings devoted exclusively to exploring the theoretical, methodological, and practical problems that arise when women utilize oral history as a tool of feminist scholarship. In thirteen multi-disciplinary essays, the book takes stock of the implicit presuppositions, contradictions, and prospects of oral history at the hands of feminist scholars.
Keywords: muistitieto; feminismi; tutkimusmenetelmät; teoriat; naiset; naistutkimus; haastattelut; elämäkertatutkimus; tutkimusetiikka; erfarenhetsberättelse; feminism; forskningsmetoder; teorier; kvinnor; kvinnoforskning; intervjuer; livshistorieforskning; forskningsetik